Structural Conformational Study of Isoflavon Derivatives in Soybean Using Semi empirical Methods - Yuyun Yuniati (Journal of Global Pharma Technology, 2018)
Isoflavon was falconoid group which was a polifenolic compound. As a member of flavonoid groups, isoflavon was a bioactive compound that contains phenolic group reported to have an  ability as antioxidant and prevent free radical damage through two mechanism. The mechanism are donating hydrogen ions and directly acting as a free radical scavenger. One of the seed plants which contain isoflavon was soybean. Isoflavon derivatives in soybean are biochanin a, genistein, daidzein, equol, formononetin, dan glycitein. The compounds can be applied in medical and pharmaceutical. Generally the is of lavon derivatives in soy bean have been conducted to anti-allergic, antioxidant, dan anti cholesterol. These studies based on optimization and structural conformational to support QSAR and Molecular docking studies. In this study, semiempirical AM1 method was used for optimization all the structure. The distance of two nearby atoms affect the structure stability and the strain energy because the lower the strain energy, the more stable that compound The most stable structure for biochanin a, genwastein, daidzein, glycitein, formononetin was 40o while the most stable structure for equol was 280o.Keywords: Conformation, Derivatives, Energy, Isoflavon, Soybean.